The Brain Dead Patient Is Still Sentient: A Further Reply to Patrick Lee and Germain Grisez. - GIORGIO AUSTRIACO, NICANOR PIER; Austriaco, Nicanor Pier Giorgio Op (Journal of Medicine & Philosophy, 2016)
Patrick Lee and Germain Grisez have argued that the total brain dead patient is still dead because the integrated entity that remains is not even an animal, not only because he is not sentient but also, and more importantly, because he has lost the radical capacity for sentience. In this essay, written from within and as a contribution to the Catholic philosophical tradition, I respond to Lee and Grisez's argument by proposing that the brain dead patient is still sentient because an animal with an intact but severed spinal cord can still perceive and respond to external stimuli. The brain dead patient is an unconscious sentient organism.